The association between multi-inflammatory index and long-term mortality in post-myocardial infarction patients treated with percutaneous coronary intervention - Hyun, Sangho; Seung, Jaeho; Lee, Kwan Yong; Kim, Sang Hyun; Lee, Myunhee; Yoon, Andrew H.; Lee, Wonjae; Hwang, Byung-Hee; Choo, Eun-Ho; Kim, Chan Jun; Kim, Jin-Jin; Park, Ha-Wook; et al. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundInflammation plays a crucial role in the pathophysiology of acute myocardial infarction (AMI), and various inflammatory markers have been associated with patient outcomes. The multi-inflammatory index (MII) has emerged as a potential prognostic indicator, but its relationship with AMI mortality remains unclear.MethodsWe analyzed 8,414 patients with successfully revascularized AMI. The subjects were divided into a high MII group (n = 3,708) or a low MII group (n = 4,706) using the MII score at admission. The MII score was calculated using the initial serum neutrophil, lymphocyte, and C-reactive protein (CRP). The primary and secondary outcomes were all-cause mortality and major adverse cardiac and cerebrovascular events (MACCE).ResultsOver a median follow-up of 5.13 years, the high MII group showed significantly higher incidences of all-cause mortality and MACCE than the low MII group (p < 0.001, each). Multivariate Cox regression identified a high MII score as an independent predictor of all-cause mortality and MACCE [adjusted hazard ratio (HR) 1.71; 95% confidence interval (CI) 1.55–1.89; p < 0.001, HR 1.53; 95% CI 1.40–1.67; p < 0.001]. MII score had statistically higher discriminative ability for predicting all-cause mortality than the conventional inflammatory marker, CRP (C-index 0.662; 95% CI 0.648–0.677 vs. 0.646; 95% CI 0.632–0.661, p < 0.001). The predictive accuracies of traditional clinical factor discrimination and reclassification for mortality were significantly improved upon the addition of high MII score (C-index 0.791 vs. 0.780; 95% CI 0.780–0.803; p < 0.001, NRI 0.018; 95% CI 0.014–0.021; p < 0.001).ConclusionIn the AMI cohort, a high MII score was strongly associated with long-term mortality and MACCE.